BEYOND PHILANTHROPY: THE ROCKEFELLER FOUNDATION'S PUBLIC HEALTH INTERVENTION IN THIRUVITHAMKOOR, 1929-1939 - Kabir, m (cdswp350, 2003)
This paper examines the public health intervention of the Rockefeller Foundation, one of the major `philanthropic' organisations in the world during the twentieth century, in the erstwhile princely state of Thiruvithamkoor, which currently constitutes a part of Kerala state in India. It discusses the specific historical context of the intervention, the methods of intervention and their outcomes. It is argued that the Foundation's interests in Thiruvithamkoor went beyond its avowed objective of philanthropy. Thiruvithamkoor provided a fertile ground to the Foundation to be used as a `tropical observatory's for research on diseases on which it had already been preoccupied. It is also pointed out that the activities of the Foundation became critical in the institutionalisation of public health in Thiruvithamkoor and in helping the region in controlling and finally eradicating some of the diseases at a later date.